PEACE ROLE OF DEITIES IN AFRICAN TRADITIONAL RELIGION (ATR) IN TRADITIONAL IGBO SOCIETIES OF NIGERIA: THE CASE OF OGHE PEOPLE IN EZEAGU LOCAL GOVERNMENT AREA OF ENUGU STATE, NIGERIA - C. chidiobi, Okechukwu; C. Ibekwe, Juliet . (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
This paper examines the peace role of African Traditional Religion (ATR) in conflict resolution and management using the traditional Oghe land in Ezeagu Local Government Area of Enugu State, Nigeria as a case study. The emphasis is however on the deities which forms the cardinal part of African traditional religion. Prior to the advent of Christianity in Oghe land and by extension the entire Igbo societies, the African traditional religion and the belief in the deities has long been with the people and is still relevant till date. Thus, Christianity as a religious system with its set of beliefs and religious life did not meet an empty Oghe mind but one which was already preoccupied with (Oghe) traditional thought. It is this preoccupied traditional religious and cultural mind which receives, understands, interprets and applies Christianity in Oghe cum Igbo land .The Oghe man worships the Supreme Deity/God through the smaller or lesser deities which act as official messengers. The deities are known to have provided peaceful resolutions to numerousconflicts situations in Oghe land which were discussed in the course of this paper. In view of this, it is however the modest believe of the authors that this article may not have captured all of the aspects of this study, but one can therefore say that the article has succeeded in extending the frontier of knowledge which other interest researchers can lend their opinion on. Other sundry but related issues like the land, culture and people of Oghe as well as the concepts of deity, peace, conflict and conflict resolution were equally looked at in this paper. This work however employed qualitative historical research methodology to interpret both the secondary and primary data gathered during this study. As young kids who grew up in Agueke; one of the villages in Iwollo, a town in Oghe land where the once famous deity known and referred to as “Ugwu-Agueke” was once domiciled, this paper therefore draws so much from reminiscence or better still an eye witness account to support the thesis presented in this paper. Innate theory, a sub branch of biological theory of conflict was adopted as a theoretical frame work to present a lucid explanation on how man’s natural instinct to survive, protect or defend what they have or how his selfish, wicked, destructive and sinful nature has been the bane of conflict in traditional Oghe land nay human societies in general. This study concluded by advocating that those aspect of traditional religion which can help to maintain order and sanity as well as create a peaceful and corruption free society devoid of conflict should be incorporated alongside the western religion; Christianity. This would avoid the situation of throwing away the baby and the birth water which this paper tried to discuss.